2013
DOI: 10.4314/ajcem.v14i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion transmissible viral infections among potential blood donors in Ibadan, Nigeria

Abstract: It is evident that proper screening procedures prior blood transfusion is a cost-effective approach for prevention and control of transfusion-transmissible infections (TTIs). Also, it has been documented that sub-standard test kits are mostly used in resource limited settings for transfusion related diagnosis. However, the role of such practice in epidemiology of transfusion transmissible viral infections in a tertiary health care facility would give an insight to the rates of blood transfusion associated vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 8 publications
6
6
1
Order By: Relevance
“…When the finding of this study compare with similar study in other countries, higher study reported from south Dar Fur 0.65% (Abou et al, 2009), Kano Nigeria 1.8% (Nwankwo et al, 2012), Ibadan Nigeria 1.4% (Afolabi et al, 2013), Akura Nigeria 2.1% (Shittu et al, 2014), Quång Trị, Vietnam 51.7% (Viet et al, 2015), Kathmandu Nepal 0.64% (Shrestha et al, 2009), Babylon Iraq 0.5% (Al-Juboury et al, 2010), Jordan 0.9% (Al-Gani, 2011),Gujarat India 0.074% (Dhruva et al, 2014), and Aden city Yemen1.3% (Al-Waleedi and Khader, 2012). Genetic diversity, socio-cultural condition may be possible factors.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…When the finding of this study compare with similar study in other countries, higher study reported from south Dar Fur 0.65% (Abou et al, 2009), Kano Nigeria 1.8% (Nwankwo et al, 2012), Ibadan Nigeria 1.4% (Afolabi et al, 2013), Akura Nigeria 2.1% (Shittu et al, 2014), Quång Trị, Vietnam 51.7% (Viet et al, 2015), Kathmandu Nepal 0.64% (Shrestha et al, 2009), Babylon Iraq 0.5% (Al-Juboury et al, 2010), Jordan 0.9% (Al-Gani, 2011),Gujarat India 0.074% (Dhruva et al, 2014), and Aden city Yemen1.3% (Al-Waleedi and Khader, 2012). Genetic diversity, socio-cultural condition may be possible factors.…”
Section: Discussionsupporting
confidence: 76%
“…When the finding of this study compare with similar study in other countries, higher study reported from south Dar fur 6.25% (Abou et al, 2009), Tete Mozambique 10.6% (Stokx et al, 2011), kano Nigeria 11.1% (Nwankwo et al, 2012), Ibadan Nigeria 5.9% (Afolabi et al, 2013), Akure Nigeria 7.4% (Shittu et al, 2014), Quång Trị, Vietnam 11.1% (Viet et al, 2015). 16-3.19 Lower finding was also reported from Kathmandu Nepal 0.47% (Shrestha et al, 2009), Babylon Iraq 0.7% (Al-Juboury et al, 2010), Jordan 1.4% (Al-Gani, 2011), Gujarat India 0.68%, (Dhruva et al, 2014).…”
Section: Discussionsupporting
confidence: 73%
“…This was the most prevalent TTI in this study. This is similar to findings from other studies in Nigeria and other developing countries like India and Pakistan . It is however different from a study from Bida in west‐central Nigeria which had HIV being the most prevalent and Mozambique where syphilis was most prevalent .…”
Section: Discussionsupporting
confidence: 92%
“…2 In University College Hospital, Ibadan, Nigeria, transmission of HIV through infected blood and its products accounts for approximately 62.0%. 3 Blood safety remains an issue of major concern in transfusion medicine in developing countries like Nigeria where national blood transfusion services, appropriate infrastructure, trained personnel and financial resources are inadequate due to poor budgetary allocation to the health sector. Sensitive tests selection will increase blood safety decreasing the window period and this can be achieved with the use of third generation ELISA tests, this will decrease window period by 3 weeks from the previously reported period of 6-8 weeks.…”
Section: Introductionmentioning
confidence: 99%